MACROZOOBENTHOS ABUNDANCE IN THE MANGROVE AREA OF TANAH MERAH SAMBOJA KUTAI KARTANEGARA EAST KALIMANTAN - Irwan Ramadhan Ritonga; Irma Suryana; Elisar Elisar (Universitas Mataram, 2024)
Tanah Merah Beach is a coastal area of Samboja in East Kalimantan, which is a local tourist destination. The association of coastal ecosystems can be shown by macrozoobenthos, as one of the biota components in coastal areas to mangroves. This study identifies the species, calculates the abundance, and analyses the ecological index of macrozoobenthos, as well as looking at the relationship between nutrients and sediment texture with the number of macrozoobenthos found. The purpose of this research is to determine the condition of nutrients in the sediment substrate to its abundance in the mangrove ecosystem area. Sampling was conducted at three points based on the percentage of mangrove canopy cover in the Monmang version 2.0 application, with each point represented by 3 quadrant points measuring 0.25 m2. The results showed that the percentage of mangrove canopy cover was categorised as slight-moderate, the abundance of individuals was dominated by the Gastropoda class with 9 species and a small proportion of the Bivalve class. The ecological indices in order are the Diversity Index (H') in the low category, Diversity (E) in the low category, and dominance (C) found Cerithidae sp species dominating each point. The highest abundance was found at radius 2 canopy cover 77.24 - 83.13%. Nutrient content in sediment, nitrate (1.00-16.25 mg/L), phosphate (29.01-83.94 mg/L), organic carbon (2.23-3.24%) with confirmed sediment texture of sandy loam. Nitrate content ranged from 1.00-16.25 mg/L, Phosphate 34.65 - 44.51 mg/L and Organic carbon 2.23-3.24% (per mg) in the sediment and a significant effect of phosphate content on Macrozoobenthos abundance was found in the correlation test results.